Down-regulation of glucocorticoid receptors in mouse lymphoma cell variants. - Danielsen, M (1984)
The mouse thymoma-derived cell line W7 is sensitive to the cytolytic action of glucocorticoids. We have isolated a novel class of cell variant that apparently overcomes its inherent sensitivity to glucocorticoids by reversibly down-regulating the level of glucocorticoid receptors. This phenotype is stable during subcloning in the presence and in the absence of glucocorticoids and is dominant in somatic cell hybrids with wild-type cells. Fusion of this variant with wild-type cells produces hybrids that down-regulate and are less sensitive to glucocorticoids than hybrids of receptor-negative and wild-type cells. This is the first demonstration of a phenotypic change which correlates with down-regulation of the glucocorticoid receptor.